Principles and Application Fields in CUDA Parallel programming and its potential - Rivera G, Iván Omar; Vargas-Lombardo, Miguel (Nexo Revista Científica, 2012)
The following monograph is a summary of recent information regarding GPU parallel processing via CUDA technology for general purpose computations, its description, as well as some applications.